Characteristics and Pollution Contribution of the Internal Nitrogen Release From the Sediments in the Dahekou Reservoir in Inner Mongolia - Lu, Junping; Liu, Tingxi; Shi, Xiao Hong; Sun, Biao; Zhao, Shengnan (Frontiers in Environmental Science, 2022)
In order to clarify the influence of overlying water environment changes on the endogenous nitrogen release from reservoir sediment in different seasons, the quantitative linear relationship between the intensity of nitrogen release from sediment and the environmental factors of overlying water was established, and meanwhile their contribution rate to nitrogen pollution of reservoirs in different storage periods. In this study, the sediment samples were collected from Dahekou Reservoir in Xilinguole League, and the orthogonal simulation experiments were carried out in laboratory. The mathematical model established by using multiple linear regression method showed that: The order of significant influence of environmental factors on sediment nitrogen release in Dahekou Reservoir is water temperature (T)>dissolved oxygen (DO)>pH value>hydrodynamic force (K). The total nitrogen release flux from sediment of Koukou Reservoir was 14.278 t/a in 2018, accounting for 27.91% of TN pollution load input in the same period. Especially in winter, the contribution rate of nitrogen release from sediment reached the highest level of 57.06-63.26%, which was significantly higher than that of river to total nitrogen pollution load of reservoir. Nitrogen release from sediment became the main source of nitrogen nutrients of reservoir in ice-sealed period.